Antecedent of Macroprudential Indicator on BAZNAS Funding Collection - Mukhamad Yazid Afandi; Nafi'ah Firahmatillah; Ahmed Abdul Malik (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to determine the macroeconomic influence in the collection of ZIS in Indonesia. This research method uses quantitative methods with panel data regression analysis models. The data consisted of 34 provinces during the 9-year study period from 2013-2021. The secondary data used comes from the publication of the annual report of BAZNAS, Regional BAZ, and also other supporting data such as BPS and BAPPENAS. The results show that simultaneously all variables have a significant effect on the collection of ZIS. Meanwhile, partially, both Human Development Index (HDI), Economic Growth, Income Per Capita (IPC), and Provincial Minimum Wage (PMW), have a positive effect on the collection of ZIS funds in BAZNAS 2013-2021. Although macroeconomics has an impact on the collection of ZIS, it is necessary to conduct further research related to community behavior with a consumer behavior approach, especially the focus on awareness instruments in paying ZIS.